Relasi Agama dan Negara dalam Sistem Hukum Indonesia: Analisis Pemikiran Muhammad Tahir Azhary - Maulana, Aris Fajar; Misran, Misran; Bin Adnan, Boihaqi (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
This study examines Muhammad Tahir Azhary’s thoughts on the relationship between religion and the state within the Indonesian legal system. The research problem focuses on the position of Islam as a normative source in the Indonesian constitutional context. The study aims to understand Azhary’s theoretical construction regarding the interaction between religion and the state and its implications for national legal practice. This research employs a conceptual approach within a normative legal framework, using primary, secondary, and tertiary legal materials analyzed descriptively and prescriptively. The findings indicate that Azhary rejects the separation of religion and the state. Through the Concentric Circle Theory, both are viewed as complementary entities interconnected constitutionally. In his view, Islam serves not only as a source of moral values but also as a normative foundation for law and state institutions, suggesting that the relationship between religion and the state must be managed fairly, inclusively, and oriented toward public welfare. The implications of this study provide a conceptual perspective for policymakers, academics, and legal practitioners to harmoniously manage the relationship between religion and the state in Indonesia